The African presence : representations of Africa in the construction of Britishness - Harrison, Graham, 1968- (Manchester University Press, 2013)
Examining the ways in which representations of Africa contribute to the changing nature of British national identity, this book uses interviews, photo archives, media coverage, advertisements and web material in order to focus on the major African campaigns: the abolition of slavery, anti-apartheid, drop the debt, and Make Poverty History.